Assessment of the fitness test 10-metre underwater run among military cadet officers - Shahrulfadly Rustam; Aiman Shahrul Hazim Mohd Sabudin; Mohd Izwan Shahril; Jorrye Jakiwa (Fizjoterapia Polska, 2025)
This study assesses the reliability of the 10-metre underwater run as a fitness test among military cadet officers, focusing on its ability to evaluate anaerobic capacity, breath-hold endurance, and adaptability to aquatic environments. As military operations increasingly require performance in water-based settings, traditional land-focused assessments may not fully capture operational readiness. The 10-metre underwater run challenges cadets to hold their breath while sprinting underwater, engaging both aerobic and anaerobic energy systems. Using a quantitative test-retest approach, 30 cadet officers from the National Defence University of Malaysia completed the test twice, with a seven-day interval. Pearson’s correlation coefficient was used to determine consistency between test sessions, resulting in a high correlation of 0.810 (p < 0.001), indicating strong reliability. This reliability supports the test as a robust tool for assessing underwater sprint capacity and breath-hold endurance. The results align with previous findings on the importance of repeatability in operational fitness tests, suggesting that the 10-metre underwater run could serve as a valuable tool in military training for evaluating cadet readiness in aquatic scenarios. Future studies could expand the sample size and explore additional variables, enhancing the understanding of performance in underwater environments and strengthening military training frameworks for diverse operational demands.